(untitled) (International Journal of Engineering and Computer Science, 2015)
The cloud computing has witnessed drastic evolution in last few years with respect to its development and application. Thus, research and development in cloud computing are scaling in a positive direction, due to the growing demand for cloud computing but no one is bothered about its impact on mental health. This paper provides the results after thorough analysis and data collection how cloud based services are acting like slow poison for mental health of youths. Youths expressed concern about the security, access to, and privacy, of their data in the cloud. The results shows that the female youth are become short tempered ever since they are using cloud based websites than male. The user have no idea about data storage in cloud technology. So end user always worry about privacy and security of data. When user use cloud base services, he/she has some mental pressure due to unknown place of data storage. Regular use of cloud base services user feel anxiety